An on-site Raman and pXRF study of Joseph Coteau and Philippe Parpette's jewelled porcelain: a summit of ceramic art - Colomban, Philippe; Kirmizi, Burcu; Clais, Jean-Baptiste; Gironda, Michele (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
Gilt-decorated porcelains of the French enamellists Joseph Coteau and Philippe Parpette, unifying metal and ceramic enamel techniques had been produced for a short time period, between similar to 1770 to 1800 AD. However, this type of production was limited and poorly documented. Their enamelled decorations consist of lead-based transparent and opaque enamels coating gold foils fired on the porcelain glaze. Rare items had been produced at different factories (Sevres Royal Factory, Comte d'Artois Factory) and it is reported that some copies had been made during the 19th century. We present here the first (non-invasive) Raman study of four cups and two pairs of vases (also analysed by pXRF) belonging to the productions from these factories. The decors made of enamel on gold foil (paillon in French) were applied both on soft-paste and hard-paste porcelain body. The bonding between the gold foil and the glaze was found to be obtained by addition of arsenic and perhaps some other fluxes (boron, bismuth?). Differences were identified in the glazing/enamelling technology. The use of cassiterite opacifier seems to be characteristic of Coteau's technique. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Porcelain; Enamel; Glaze; On-site raman; Pigments; Gold; EUROPEAN COBALT SOURCES; COMPOSITIONAL ANALYSIS; LIMOGES ENAMELS; PORTABLE XRF; IDENTIFICATION; SPECTROSCOPY; DIFFERENTIATION; ANCIENT; 15TH; SILICATES; Archaeology; Art; Chemistry; Geology; Materials Science